Assessment of Motor Repertoire in 3- to 5-Month-Old Infants With Obstetric Brachial Plexus Lesion. Issue 2 (April 2020) - Kahraman, Aysu; Mutlu, Akmer; Livanelioğlu, Ayşe
Abstract : Purpose: The aim of this study was to define the movement characteristics and postures of infants with obstetric brachial plexus lesion. Methods: The study group included 20 infants with obstetric brachial plexus lesion and a control group of 20 infants with normal neurological outcome, aged 9 to 17 weeks postterm. Infants were evaluated by global and detailed general movements assessment. Results: There were no significant differences between the motor optimality scores of the 2 groups. However, there were some differences in terms of concurrent movements and the posture. Infants with obstetric brachial plexus lesion demonstrated more excitement bursts, head rotation, hand-knee contact, rolling, and few finger posture and postural asymmetry, and performed jerky movements when compared with the control group. Conclusions: Obstetric brachial plexus lesion did not affect the quality of fidgety movements of the infants but leads to compensatory movements in concurrent movements on the unaffected sides. Abstract : The aim of this study was to define the movement characteristics and postures of infants with obstetric brachial plexus lesion.